CRISPR/Cas9 in plants: at play in the genome and at work for crop improvement. (17th April 2018) - Hussain, Babar; Lucas, Stuart James; Budak, Hikmet
Abstract: The clustered regularly interspaced short palindromic repeats/CRISPR-associated protein 9 (CRISPR/Cas9) system uses single-guide RNAs for genome editing, making it a simple, robust, powerful tool for targeted gene mutagenesis, knockout and knock-in/replacement, as well as transcriptional regulation. Here, we review the working principles, components and potential modifications of CRISPR/Cas9 for efficient single and multiplex gene editing in plants. We also describe recent work that has used CRISPR/Cas9 to improve economically important traits in crop plants. Although the apparent ease of CRISPR/Cas9-mediated editing may make it appear as though scientists are merely playing with plant genomes, the combined power of CRISPR/Cas9 has enabled vital research to be completed in the battle toward optimization and adaptation of crop species, permitting crucial advances to be achieved in crop improvement.